Effects of long-term green manure application on the content and structure of dissolved organic matter in red paddy soil - Song-juan GAO; Ju-sheng GAO; Wei-dong CAO; Chun-qin ZOU; Jing HUANG; Jin-shun BAI; Fu-gen DOU (Journal of Integrative Agriculture, 2018)
Dissolved organic matter (DOM) plays important roles in soil biogeochemistry activity and nutrients transportation in soils, but studies regarding the long-term effects of green manures on the content and structure of DOM in red paddy soil have not been reported yet. A long-term green manure experiment established in 1982 was utilized to test the DOM contents in different treatments, and the spectral characteristics of DOM were investigated by using ultraviolet-visible (UV-Vis) spectrometry and Fourier transform infrared (FTIR) spectrometry. The experiment included four cropping systems: rice-rice-milk vetch (RRV), rice-rice-rape (RRP), rice-rice-ryegrass (RRG) and rice-rice-winter fallow (RRF), among them, milk vetch, rape, and ryegrass are popular winter green manure species in southern China. The results showed that the content of dissolved organic carbon (DOC), which is widely used to estimate the concentration of DOM, was significantly promoted after the incorporation of green manures compared with the other sampling stages. The contents of aromatic groups and the degree of humification of DOM increased in RRV and RRP, suggesting more complex compositions of the soil DOM after long-term application of milk vetch and rape. The contents of phenol, alcohol and carboxylic acid group at the mature stage of early rice were significantly higher than those at the stage of after green manures turned over, especially for the RRV treatment. The absorption ratio of FTIR indicated that winter plantation of rape increased the aromatic-C/aliphatic-C ratio, and ryegrass increased the aromatic-C/carboxyl-C ratio. In conclusion, long-term planting of milk vetch and rape as green manures increased the degree of aromaticity, humification and average molecular weight of DOM, and made the DOM more stable in red paddy soil.